The measurement of the professional competence formation of future geography teachers by qualimetry means - Borysenko, K. (Problems of Engineer-Pedagogical Education, 2019)
The article analyzes problems of the professional competencies formation of the future geography teacher in the process of educational practices based on a qualimetric approach. The place of professional competencies that are formed during training practices in the competence model of the future geography teacher is substantiated. For use, a factor-criterion model was proposed for assessing the level of formation of the special competencies of a future geography teacher based on the results of educational practices in undergraduate conditions and provided its theoretical justification. The paper also presents a mechanism for adjusting the educational process based on the results of the introduction of technology to form the special competencies of a future geography teacher as a result of educational practices. The existing algorithm for the development measuring of professional competencies of future geography teachers provides for the end-to-end implementation of the formation technology of professional competencies during the entire training time devoted to educational practices. In addition, it provides the repetition of certain theoretical material, which is necessary for solving competence-related tasks that related to practice managers, contributes to the students better learning of knowledge and skills, the formation of certain personal qualities and leads to an improvement in the quality of the educational process and as its result - the formation of individual professional competencies as part of the integral competence of a graduate undergraduate program in the specialty "Geography".